Faktor-Faktor Yang Berhubungan Dengan Kejadian Jatuh Pada Lansia - Sugeng Riyadi; Subandiyo Subandiyo; Ruti Wiyati (JURNAL KEPERAWATAN MERSI, 2021)
Background:  Elderly people often experience serious health problems, one of which is frequent falls. Falls in the elderly can lead to serious problems. The incidence of falls in the elderly can affect sensing factors including vision problems, hearing problems, an-nahl and nervous system disorders, and impaired walking processes.Methods: This study aims to determine the causes and factors of falls in the elderly. research design using quantitative analytic design with a cross sectional approach. The population of this study is the elderly group whose samples were taken using purposive random sampling analysis which was used to determine differences and risk factors using the Chi square test.Results: research that obtained di is known as much as 69%. of those who fall will experience a change in vision as much as 70%. the elderly who have hearing loss as much as 57%. neuromuscular disorders 81%. the elderly who use Walker 80% of the elderly who experience environmental orientation disorders as much as 50%.Conclusion: Based on the results of the study, it is known that the causes of elderly falls can be anticipated with posbindu activities. In the activities of bindu patients, health education can be provided to the elderly and their families about the risk of falling. The risk of falling is a process that occurs in the elderly due to the aging process, this must be known by the family so that every family member can help the elderly to reduce the risk of falling.